The Effectiveness of Supervisory Methods on Teachers’ Performance in Schools Affiliated with the Al-Ulaya Education Office in Riyadh - Al-Fadhil, Abdulaziz Nasser (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the effectiveness of various supervisory methods—namely classroom visits, demonstration lessons, workshops, and educational meetings—in improving the performance of teachers at the Al-Olaya Education Office, from their own perspective. The researcher adopted the descriptive survey method and used a questionnaire administered to a sample of 316 general education teachers across all three school levels during the academic year 1446 AH. The study’s findings revealed that the overall effectiveness of the supervisory methods on teachers’ performance in schools under the Al-Olaya Education Office in Riyadh reached a mean score of 3.99 out of 5, indicating a high level of effectiveness. Among the individual methods, the "demonstration lesson" was rated the most effective with a mean score of 4.31 (very high effectiveness), followed by "workshop" (4.11), then "educational meeting" (4.08), and finally "classroom visit" (3.47); all were rated as highly effective. Based on these results, the researcher recommended enhancing transparency in evaluation processes so that both teachers and school principals can clearly identify areas of weakness to address and strengths to reinforce. Furthermore, the study emphasized the importance of identifying training needs and continuously evaluating and developing supervisory methods whenever necessary.